Natur, religion, medien : transformationen frühneuzeitlichen wissens - Burkard, Thorsten (Diskursivierung von Wissen in der Frühen Neuzeit, 2013)
In the early modern period, knowledge became more differentiated in form and content. Contemporaries did not fail to remark on the benefits and problems of a process that impacted various domains of knowledge, and that was determined by technological and institutional factors, among others. The essays in this volume examine organizational forms and describe media-based discursive processes through examples drawn from different types of knowledge.